Nurses’ perception of the professional practice environment and its relation to organizational dehumanization and work passion - Shimaa Mohamed Salem; Huda Mohammed Bakeer; Hayam Ahmed El Shrief (BMC Nursing, 2025)
Abstract Background A professional practice environment enhances health worker recruitment and retention and contributes to quality patient care and health system strengthening. Hence, improving the professional practice environments of nurses at hospitals could improve the performance of the health system, increase work passion, and decrease organizational dehumanization. Aim To assess nurses’ perceptions of the professional practice environment and its relation to organizational dehumanization and work passion. Method A descriptive correlational research design was used. A convenience sample of staff nurses (n = 274) was recruited who worked in critical care units and inpatient departments at the National Liver Institute (NLI) in Shebin Elkom city/Menoufia Governorate, Egypt. Three instruments were used: the nursing professional practice environment questionnaire, the organization dehumanization scale, and the work passion scale. Results More than two-thirds of the study subjects (72.3%) reported a favorable professional practice environment. The highest mean score and first ranking was related to the dimension of teamwork. The lowest mean score and lowest rank was associated with communication about patients. Additionally, more than two-thirds of the nurses studied perceived a feeling of not being dehumanized by their organization and a high level of passion toward their work (63% and 71.6%, respectively). Conclusion There was a statistically significant negative correlation between the professional practice environment and organizational dehumanization. Moreover, there was a statistically significant positive correlation between the professional practice environment and work passion. Implication for nursing practice Managers must design interventions to teach staff members that they are valued as individuals rather than expendable goods. To make staff members feel less dehumanized and more supported, hospitals and their managers may apply particular human resources practices, such as lowering workload, enhancing job stability, and providing training and development opportunities for their growth and grooming.